TOBACCO CONSUMPTION AND ASSOCIATED MORBIDITIES-A COMMUNITY BASED CROSS SECTIONAL STUDY AMONG RURAL AGRICULTURAL WORKERS IN NORTH KARNATAKA - KULKARNI RAJESH R. (International Journal of Pharma and Bio Sciences, 2013)
Background and aims: 72% of Indian population lives in rural areas, where their main occupation is agriculture. In developing countries like India, tobacco consumption is mainly done in two forms: smoked tobacco products and smokeless tobacco. In India, tobacco consumption is responsible for half of all the cancers in men and a quarter of all cancers in women. Very few community based studies have been conducted to assess the prevalence of the tobacco use and their associated morbidities among agricultural workers.Methods and Material:This cross-sectional study was done from January 2009 to December 2009 among 400 agricultural workers of age 16 to 60 years residing in a sub-centre area of the PHC administrated by Medical College in South India, using predesigned and pretested questionnaire. Statistical analysis was done by using percentages and chi square test.Results: Among the study participants 55.75% were men and 44.25% were women, with male to female ratio of 1.25:1. Most of the agricultural workers (89.5%) were Hindus and 47% were illiterates; of the 400 study participants, 295 (73.75%) belonged to Class V socio-economic status. 55.75% had the habit of consuming smokeless tobacco. Among them 98(38.7%) had the habit of chewing gutkha, 83(32.8%) chewed pan masala and remaining 28.4% betel quid. Common reasons for using tobacco were to experiment in 43.4%, 36.3% because of influence of family members and 20.1% because of the influence of friends. Majority (62%) of agricultural workers suffered from morbidities associated with oral cavity, followed by morbidities associated with musculoskeletal system (21.7%) and respiratory system (19%). Increasing age, gender and poor educational status were significantly associated with morbidities of the oral cavity. Conclusion:There is widespread belief that smokeless tobacco use is less harmful than smoking. There needs to have an end of this belief. Which can be achieved by Strengthening the information, education and communication (IEC) activities and special health check-up camps with emphasis on improvement of health.